Biodistribution of a radiolabelled thermoresponsive polymer in mice - Kucka, Jan; Hrubý, Martin; Lebeda, Ondrej (Applied radiation and isotopes, 2010)
Drug delivery systems based on thermoresponsive polymers might serve as suitable carriers for local radiotherapy. We have, therefore, designed and synthesized a radioiodine-labellable thermoresponsive polymer. The polymer was synthesized by copolymerization of N-isopropylacrylamide with N-methacryloyl tyrosinamide in tetrahydrofuran, and then labelled by (131)I. The solution of this labelled polymer in dimethylsulfoxide (4.4 MBq/ml; 1.8 wt% polymer) was applied to femoral muscle of male Balb/C mice (50 microl per animal). The biodistribution and excretion of radioactivity was followed in 2h and 1, 7, 14, 28 and 42 d post injection (n=6 per time point). As expected, the labelled polymer was left on the application site (ca 90% 2h post injection), decreasing slowly to ca 80% within 14 d. At 28 d post injection, ca 70% of the injected activity was still found on the application site, decreasing to ca 60% at 42 d. No organ-specific accumulation of the radioactivity released from the application site, including thyroid, was observed. Majority of the released radioactivity was excreted via urine and faeces. This preliminary study suggests that thermoresponsive polymers could be used as an effective delivery system for localized radiotherapy.
Keywords: akrylové pryskyřice; methakryláty; radioterapie; Iodine Radioisotopes; Temperature; Tyrosine; teplota; tkáňová distribuce; myši inbrední BALB C; Drug Delivery Systems; zvířata; myši; Radiotherapy; radioizotopy jodu; Mice; Acrylamides; Acrylic Resins; akrylamidy; kosterní svaly; Male; lékové transportní systémy; Muscle, Skeletal; Animals; mužské pohlaví; radiofarmaka; Methacrylates; tyrosin; Tissue Distribution; Mice, Inbred BALB C; Radiopharmaceuticals